A study on the influence of the use of the UP College of Education Library on the reading habits of UP Education students - Talan, Jena V. (School of Library and Information Studies, University of the Philippines Diliman, 2010)
Educators play a role in molding their pupils' values and one way of attaining this is by setting an example. The same can be said for reading habits and attitudes. This study was done with the objective of determining the reading habits, as well as the library usage, of the students from the College of Education University of the Philippines Diliman.